Perencanaan Dimensi Saluran Drainase Jalan Simpang Seputuk KTT KALTARA Sebagai Penunjang Kegiatan Penanggulangan Banjir (STA 200 - 4 + 400) - Sulistyani, Kiki Frida; Rahma, Pamela Dinar; Sinambela, Despari (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2023)
Drainage is one aspect that is meaningful in supporting the infrastructure of an area or region. This study aims to determine the existing condition of the channel and plan the dimensions of the drainage channel that can accommodate flood discharge. This research was carried out in several stages. The first stage, data collection in the form of secondary data, then in the second stage, data analysis is carried out, namely hydrological analysis and hydraulics analysis and the third stage is carried out planning channel dimensions with a trapezoidal cross section. From the results of the analysis and calculations, it was found that the flood discharge of the left segment channel was Qr5 th = 4.3359 - 25.6183 m3 / sec and Qr10 th = 4.9244 - 29.0951 m3 / sec and the flood discharge of the right segment channel Qr5 th = 3.9575 - 9.4389 m3 / sec and Qr10 th = 4.4946 - 10.7199 m3 / sec. In the dimensions of the drainage channel, the left segment has 7 channel segments with a cross-sectional width of the channel (B) = 3.50 m - 5.00 m and a channel depth (H) = 1.30 m - 2.80 m, while the right channel segment has 6 channel segments with a cross-sectional width of the channel (B) = 4.00 m - 5.00 m and channel depth (H) = 1.50 m - 3.00 m. Abstrak Drainase merupakan salah satu aspek yang berarti dalam mendukung infrastruktur suatu wilayah ataupun kawasan. Penelitian ini bertujuan untuk mengetahui kondisi eksisiting saluran dan merencanakan dimensi saluran drainase yang dapat menampung debit banjir. Penelitian ini dilakukan dalam beberapa tahapan. Tahapan pertama, pengumpulan data berupa data sekunder, kemudian pada tahap kedua, dilakukan analisis data yaitu analisis hidrologi dan analisis hidrolika dan tahap ketiga dilakukan perencanaan dimensi saluran dengan penampang berbentuk trapesium. Dari hasil analisis dan perhitungan didapatkan debir banjir saluran ruas kiri adalah Qr5 th = 4,3359 - 25,6183 m3/det dan Qr10 th = 4,9244 - 29,0951 m3/det dan debit banjir saluran ruas kanan Qr5 th = 3,9575 - 9.4389 m3/det dan Qr10 th = 4,4946 - 10,7199 m3/det. Pada dimensi saluran drainse ruas kiri memiliki 7 ruas saluran dengan lebar penampang saluran (B) = 3,50 m - 5,00 m dan kedalaman saluran (H) = 1,30 m - 2,80 m sedangkan pada ruas saluran kanan memiliki 6 ruas saluran dengan lebar penampang saluran (B) = 4,00 m - 5,00 m dan kedalaman saluran (H) = 1,50 m - 3,00 m.